Juan José Elguezabal, gobernador del Estado de Coahuila y Texas, á todos sus habitantes. SABED: Que el Ecsmo. Sr. presidente de la república, en consecuencia de los tratados celebrados el seis de noviembre pasado entre el gobierno de mi cargo . - Lombardo, Francisco María, 1799-1855 ([publisher not identified], 1834)
Includes orders from President of Mexico, by his Secretario de Estado y Relaciones, Francisco María Lombardo, directing Govenor Elguezabal to call elections which will form a new government for Coahuila y Texas. A dispute between two factions had resulted in one group forming a new government in Saltillo which had nearly lead to open warfare between to two parties. With a negiociated resolution agreed upon, the election would decide the make-up of the government to reside in Monclova, as in the past.